Arqueologita: as idiossincrasias interculturais do GITA: Grupo de Investigação do Treinamento Psicofísico do Atuante a partir dos rumos do treinamento psicofísico para atuantes de Phillip B. Zarrilli - Edson Fernando Santos da Silva (2019)
The notation of this research had as objective to present the systematization of the psychophysical training with asian meditative and martial arts for actors of the North American director, professor and performer, Phillip B. Zarrilli (1947), problematizing it from the intercultural idiosyncrasies developed in the creative practice of the Grupo de Investigação do Treinamento Psicofísico do Atuante – GITA (Investigation Group of Actor Psichophysical Training), group based at the Escola de Teatro e Dança da UFPA - ETDFUPA, (School of Theater and Dance of Pará Federal University) in the city of Belém, state of Pará, northern Brazil. The neologism “Arqueologita” is an invention of this research and it is given by the agglutination of the terms “ARQUEOLOGIA” (Archeology) and “GITA” thus composing a poetic license based on a popular expression used in the state of Pará, used to determine small things, “gitos”, “gititos” or “gitinhos”, that is, very small. An “Arqueologita” therefore, indicates that the study was developed as a "small archeology", a specific investigation that excavated the creative practice of the GITA considering its relationship with ETDUFPA and the acting paradigm of the city of Belém, cultural factors that produced displacements, discontinuities and fissures between GITA modus operandi and the psychophysical acting thought/practice of Zarrilli. Thus established, the research unfolded in two “arqueologitos” sites: in the first, entitled "Zarrilli com açaí" the emphasis shifts to GITA's close relationship with the paradigm of acting present in the city of Belém and its autopoetic spaces of political resistance, to then analyze and problematize how this causes the discontinuities and fissures between the group's creative practice in the five creative processes of theatrical montages produced until 2017 and Zarrilli's work/practice. The research was developed adopting the post-positivist/qualitative art research paradigm and, therefore, privileged the embodied dimension of the experience of the subjects involved in the research, that is, the researchers involved in the creative processes of GITA and the other local artists who were interviewed. By this paradigm the research resorted to different modes of writing here called “excavation plan”, strategies that sought to establish direct approximations with the image of the subjects involved. Strategies of writing, therefore, that seek to avoid the traditional dualisms that irretrievably split the studied object (passive, controllable and observable) of the (active) researcher who analyzes it at a distance. Due to this bias, the research adopted the “methodological bricolage”, that is, multiple procedures to portray the various archaeological sites that will be portrayed throughout the notation of the thesis.